AN ANALYTICAL STUDY OF E-COMMERCE IN ALGERIA: BETWEEN REALITY AND ASPIRATIONS - Mourad Kreifeur,; Taha Hacene, (International Journal of Innovative Technologies in Social Science, 2025)
This study examines the efforts exerted by the Algerian authorities in developing the infrastructure for e-commerce as well as the advancements in electronic payment systems that have contributed to the widespread adoption of this form of commerce. The study aims to identify the endeavours undertaken by Algeria in the development of e-commerce and electronic payment methods, in addition to diagnosing the current state of this commerce and the factors enabling its development. The findings of this study indicate that Algeria has made significant progress in terms of e-commerce infrastructure, the development of electronic payment methods, and their increased dissemination. However, these efforts are deemed insufficient, as Algeria still ranks relatively low at the global level in the field of e-commerce.